The Development of the Virtual Notebook, a Wiki-Based Ready Reference Technology - Bejune, Matthew M.; Morris, Sara E. (Reference and user services quarterly, 2010)
Traditionally, library professionals have used a variety of ready reference technologies to assist in providing reference and user services. Technologies such as card files, vertical files, and reference notebooks are frequent components of library service desks. Ready reference technologies serve many purposes, most notably, helping staff to answer frequently asked questions and facilitating the sharing of information between library staff. This paper traces the development of the Virtual Notebook, a wiki-based ready reference technology, at Purdue University. The tool is placed within the historical context of ready reference technologies within the library profession and at Purdue. The authors present preliminary results from the implementation of the Virtual Notebook and discuss the tool's future. The manuscript is an outgrowth of a presentation at the 2008 Brick and Click Symposium at Northwest Missouri State University.